Comparison and Analysis of Sub-optimal performance of OFDM/SDMA uplink System that use Conventional Multiuser Detection Techniques - et. al., Shahnaz K V, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The major challenge in the practical accomplishment of OFDM/SDMA system depends on the efficient implemen- tation of a multiuser detection (MUD) technique that separates the spatially multiplexed signal streams. Several algorithms for MIMO detection for spatially-multiplexed signals have been developed till today. The MIMO MUDs that are mostly used in previous research works and practically used are minimum mean squared error (MMSE), decorrelator (ZF), Vertical-Bell laboratories layered space-time (V-BLAST), successive inter- ference cancellation (SIC) and maximum likelihood detection (MLD). MMSE and ZF are linear MIMO detection techniques, while the remaining procedures are non linear techniques. All MUD techniques in general can be explained as a solution to a quadratic optimization problem in most cases. In this work, basic principles of ZF, MMSE, ZF-OSIC, MMSE-OSIC and ML have been explained briefly and a comparison of their performances have been done. Although the detection techniques evolved so far are matured in theory, their implementation in a real-time scenario is still challenging. It is analyzed in this paper that the poor BER results of sub-optimal detection method in comparison to MLD is due to bad channel effects.